Abdominal Cocoon Syndrome - Pokharel, Pratit; Bista, Yogendra; Desar, Rabindra; Benjankar, Raj Babu; Sharma, Pradip (Journal of Nepal Health Research Council, 2019)
Abdominal cocoon syndrome is rare cause of intestinal obstruction characterized by small bowel encapsulation by a fibro-collagenous membrane or “cocoon”.A 30 yearman presented in emergency department with abdominal pain. Preoperatively contrast enhanced computed tomography of abdomen revealed encapsulated cluster of mildly dilated and edematous small bowel loops with multiple air fluid levels with thin membrane and crowding of mesenteric vessels in left upper quadrant.Intra-operatively, the entire small bowel was found to be encapsulated in a dense fibrous sac. The peritoneal sac was excised, followed by lysis of the inter-loop adhesionswith smooth postoperative recovery.High index of suspicion is required in patient presenting with features of recurrent acute or chronic small bowel obstruction for diagnosis of abdominal cocoon syndrome. Contrast enhanced Computed Tomography of abdomen is a useful radiological to aid in preoperative diagnosis of syndrome. Keywords: Abdomen; abdominal cocoon; CECT; encapsulated cluster.